ACADEMIC ACHIEVEMENT OF REGULAR AND SPECIAL NEEDS STUDENTS IN INCLUSIVE AND NON-INCLUSIVE CLASSROOM SETTINGS - Ekeh, P. U.; Oladayo, O. T. (European Scientific Journal, ESJ, 2013)
This is an ex post facto research designed to determine the extent to which regular (normal) pupils and special needs pupils (visual and hearing impaired) in inclusive and non inclusive classrooms differ in their academic achievement. It was carried out in Port Harcourt, Rivers State of Nigeria. The population of the study consisted 206 primary 5 pupils (63 special needs pupils and 95 regular pupils from two privately owned inclusive schools, one government owned special school and one public (regular) primary school. A sample of 158 pupils made up of 63 special needs pupils (27 from inclusive schools and 36 from special school); and 95 regular (Normal) pupils (39 from the inclusive schools and 56 from the regular (non-inclusive) public primary school was used for the study. Purposive and simple random sampling techniques via balloting were used to draw the sample. Three research questions and three null hypotheses guided the study. Data of the study were obtained from the 2010/2011 promotion examination scores records of students, as maintained in the schools under study. Mean (x), Standard deviation (SD) and t-test were used to answer the research questions and test the null hypotheses respectively. Results got after data analysis indicated that significant difference existed in the academic achievement of regular and special needs students in inclusive classroom setting, in favor of the regular pupils; significant difference existed in the academic achievement of special needs pupils in inclusive and non-inclusive classrooms, in favor of those raised in inclusive classrooms; regular pupils raised in inclusive and non-inclusive classrooms differed significantly in their academic achievement, in favor of those in inclusive classrooms. Based on these results, recommendations were made including that regular and special needs students should be brought together in inclusive classrooms; regular and special education teachers should be employed to teach students in inclusive classrooms and workshops and trainings should be organized for academic and non-academic staff in inclusive schools.